Mapping the current status and outlook of research on noonan syndrome over the last 26 years: a bibliometric and visual analysis - Cui, Zhengjiu; Wang, Yuanyuan; Luo, Fei; Diao, Juanjuan; Yuan, Bin (Frontiers in Genetics, 2024)
BackgroundNoonan syndrome (NS) is a rare group of autosomal genetic disorders. In recent years, with the exploration and development of molecular diagnostic techniques, more and more researchers have begun to pay attention to NS. However, there is still a lack of reports on the bibliometric analysis of NS worldwide. This study aims to assess the current research status and development trend of NS, to explore the research hotspots and emerging topics, and to point out the direction for future scientific research.MethodsWeb of Science Core Collection was selected as the search database for bibliometric analysis of NS-related publications from 1998 to 2023. Statistical and visual analysis of the number of publications, countries, institutions, authors, journals, keywords, and references were analyzed using Citespace, VOSviewer, Scimago Graphica, and BibliometrixR.ResultsA total of 2041 articles were included in this study. The United States had the highest number of publications, and Istituto Superiore di Sanità, Italy, was the institution with the highest number of publications. TARTAGLIA M was the scientist with the highest number of publications and citations. Among the journals, AMERICAN JOURNAL OF MEDICAL GENETICS PART A has the highest output, and Nature Genetics is the most frequently cited. The reference with the highest outburst intensity is Roberts AE, LANCET, 2013. the cluster diagram divides all the keywords into seven categories, with the most vigorous outburst being “of function mutations.”ConclusionResearch hotspots in the field of NS focus on the correspondence between NS genotype and phenotype and the precise diagnosis of NS. Future research efforts will explore more deeply from the perspective of long-term intervention strategies for NS. There is an urgent need to rely on significant research countries, institutions, journals, and authors to lead the construction of a more robust global collaborative network that will enhance research efficacy.